Phosphatidylinositol 3-kinase-δ (PI3K-δ) is a potential therapeutic target in adult T-cell leukemia-lymphoma - Hiroo Katsuya; Lucy B. M. Cook; Aileen G. Rowan; Yorifumi Satou; Graham P. Taylor; Charles R. M. Bangham (BMC, 2018)
Abstract The prognosis of adult T-cell leukemia-lymphoma (ATL) remains very poor, and there is an urgent clinical need to investigate novel therapies for ATL. The expression of phosphatidylinositol 3-kinase-δ (PI3k-δ) is normally restricted to hematopoietic cells and is known as a key determinant of cell survival in certain cancers. The inhibitor of PI3k-δ, idelalisib, has been shown to be effective in the treatment of chronic lymphocytic leukemia. Here, we report the expression of PI3k-δ and the ability of idelalisib to promote apoptosis in ex vivo ATL samples. The activity of PI3K was quantified by a PI3-Kinase Activity ELISA kit. Although there was no significant difference in mean PI3K activity between healthy donors and patients with ATL, certain cases of ATL showed extremely high PI3K activities. The expression of PI3k-δ protein was detectable in most ATL cases. The freshly isolated cells from ATL patients were cultured with or without idelalisib for 0-10 days, and cell survival was then quantified. Idelalisib induced apoptosis in ATL cells in a time-dependent manner, and significantly reduced the frequency of viable ATL cells at 10 days. No time-dependent effects of idelalisib were observed in non-malignant T cells from the same patients. CCL22 has been reported to promote survival of ATL cells in part through the PI3K-AKT pathway. Idelalisib blocked this CCL22-induced phosphorylation of AKT and significantly inhibited the proliferation of ATL cells. These results validate the PI3K-AKT pathway as a potential therapeutic target in ATL.